Kajian Naratif Kehidupan Rasul Paulus - Kristiana Anik; Joko Santoso (Sekolah Tinggi Theologia Nazarene Indonesia, 2022)
The complexity of socio-anthropological variables in society requires studies and development of a missiological approach as an effort of conveying the Great Commission of the Jesus Christ. On the one hand, there is an aptness that the old approaches and mission patterns are no longer relevant applied in particular contexts. On the other hand, contextualization and new proposed approaches lead to syncretism and various missiological distortions. Paul is an apostle, theologians, and practitioners who can be seen as a model in missiological field. The purpose of this research is to find references in the mission specifically related to the paradigm, motivation, and action of Paul in the mission field. The research method employed is qualitative with biographical narrative design. It applied to obtain missiological patterns and concepts from biblical narratives on the life and writings of the Apostle Paul. This study found that Paul was a theologian as well as a missionary practitioner. The productive life of the Apostle Paul in the mission field was driven by a clear paradigm and a strong motivation so that it was actualized in his effective missiological endeavors as long as he lived.